Le lieu en projet. - Galerie L'A, Liège; Kroll, Pierre (Liège : Galerie L'A, 1984)
Antaki, M. ; Bianchini, Georges ; Boulanger, Michel ; Chaumont, H. ; Claes, P. ; Clareboudt, Jean ; Cuvelier, Werner ; Debanterlé, René ; De Grave, G. Defawes / A. ; Delhez, Y. ; Deprez, Koen ; C, R. Frei / ; Hunziker ; Salemi, M. Garzaniti / P. Hebbelinck / J.-C. ; Gillet, Jacques ; Goris, Klaas ; Kroll, Pierre ; Lacroix, C. ; Moffarts, Michel ; Mottard, N.-J. ; Ransonnet, Jean-Pierre ; Robbrecht & Daem ; Rousseff, Juliette ; Ruggeri, Laura ; Soccol, F. ; Vandeloise, Guy ; Van Geluwe, Johan ; Van Look, J. ; Van Severen, Dan ; Wuidar, Leon
Le lieu en projet, Galerie L'A, Liège, 30 mars - 18 avril 1984
Frans
boek